Keefektifan Permainan Monopoli Dalam Pembelajaran Kosakata Bahasa Jepang Siswa Kelas Viii SMP YLPI Perhentian Marpoyan - Dinda Tirta Ayu; Nana Rahayu; Sri Wahyu Widiati (Jurnal Pendidikan Indonesia, 2022)
Japanese is one of the foreign languages that is applied at several levels of education in Indonesia. For beginners, learning Japanese is taught in the form of katakana letters, hiragana letters, basic kanji letters, vocabulary, and basic grammar. The large number of vocabulary in each learning material causes students to have difficulty remembering every vocabulary learned, due to the limited media in teaching vocabulary, and the lack of precise methods used by the teacher in the teaching and learning process. One of the media used is the game. This study aims to describe 1.) To describe the vocabulary mastery of students of SMP YLPI Perhentian Marpoyan class VIII before the application of the game of monopoly; 2.) Describing the vocabulary mastery of students of SMP YLPI Perhentian Marpoyan class VIII after the application of the game of monopoly; 3.) Describe the significance level of the game of monopoly on the ability of Japanese vocabulary mastery of students of SMP YLPI Perhentian Marpoyan class VIII. The results showed that 1.) Prior to the application of the game of monopoly, the average pretest achieved by students was 39.3 in the very poor category; 2.) After the implementation of the monopoly game, the average posttest achieved by students was 85.3 with a very good category; 3.) The significance level of the monopoly game is known that the value of sig (2 - tailed) is 0.000 < 0.05